Assessment of Lifetime Attributable Risk for Public Health Sustainability from the Fukushima Accident - Faith Rukundo; Juyoul Kim (Science and Technology of Nuclear Installations)
The study aimed at reassessing the radiological risk from exposure to ionizing radiation from Fukushima Daiichi nuclear power plant accident. The estimated risks from the study were compared with World Health Organization (WHO) risk assessment estimates for validity and verification. A Radiation Risk Assessment Tool (RadRAT) was used to estimate Lifetime Attributable Risks (LAR) of cancer upon exposure. All solid cancers, leukemia, and thyroid cancer risks for ages of 1, 10, and 20 years (infants, children, and adults) in 100,000 persons at exposure were estimated. For solid cancers, LAR (10−2) was estimated in a range of 0.223∼0.668 and 0.345∼1.24 for males and females, respectively, whereas the LAR (10−2) for leukemia was estimated at 0.0155∼0.055 and 0.0118∼0.0375 for males and females, respectively. LAR (10−2) for thyroid cancer ranged from 0.0722∼0.545 and 0.0369∼0.265, respectively.